Improvement of the Technology of Production of High-Quality Potassium Chloride from Sylvinite of the Tyubegatan Deposit (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article presents the physicochemical principles of various methods for obtaining gallurgic potassium chloride. Theoretical justification for the process of obtaining high-quality pure potassium chloride by dissolving potassium chloride flotation cake. Justification of optimal technological parameters for obtaining potassium chloride by gallurgic methods.The influence of process parameters on the granulometric composition of white crystalline potassium chloride was studied.